Early Introduction of Multi-Allergen Mixture for Prevention of Food Allergy: Pilot Study - Quake, Antonia Zoe; Liu, Taryn Audrey; D’Souza, Rachel; Jackson, Katherine G.; Woch, Margaret; Tetteh, Afua; Sampath, Vanitha; Nadeau, Kari C.; Sindher, Sayantani; Chinthrajah, R. Sharon; Cao, Shu (Nutrients, 2022)
The incidence and prevalence of food allergy (FA) is increasing. While several studies have established the safety and efficacy of early introduction of single allergens in infants for the prevention of FA, the exact dose, frequency, and number of allergens that can be safely introduced to infants, particularly in those at high or low risk of atopy, are still unclear. This 1-year pilot study evaluated the safety of the early introduction of single foods (milk, egg, or peanut) vs. two foods (milk/egg, egg/peanut, milk/peanut) vs. multiple foods (milk/egg/peanut/cashew/almond/shrimp/walnut/wheat/salmon/hazelnut at low, medium, or high doses) vs. no early introduction in 180 infants between 4–6 months of age. At the end of the study, they were evaluated for plasma biomarkers associated with food reactivity via standardized blood tests. Two to four years after the start of the study, participants were evaluated by standardized food challenges. The serving sizes for the single, double, and low dose mixtures were 300 mg total protein per day. The serving sizes for the medium and high dose mixtures were 900 mg and 3000 mg total protein, respectively. Equal parts of each protein were used for double or mixture foods. All infants were breastfed until at least six months of age. The results demonstrate that infants at either high or low risk for atopy were able to tolerate the early introduction of multiple allergenic foods with no increases in any safety issues, including eczema, FA, or food protein induced enterocolitis. The mixtures of foods at either low, medium, or high doses demonstrated trends for improvement in food challenge reactivity and plasma biomarkers compared to single and double food introductions. The results of this study suggest that the early introduction of foods, particularly simultaneous mixtures of many allergenic foods, may be safe and efficacious for preventing FA and can occur safely. These results need to be confirmed by larger randomized controlled studies.